Manga guide to marketing - Yasuda, Takashi (Marketing consultant) (John Wiley & Sons, Inc., 2023)
"Marimo, comes home mentally drained after being laid off from her job. Her father runs Japanese candy business, facing a severe decline in customers and acquisition threat from a local competitor. One night, Marimo doses off in her bedroom. In her dream, she meets the mysterious duo of Rosie and Emo. From them, she learns how to rebuild her family's business through marketing, and starts to put it into practice, step by step"--